The Effectiveness Of Direct Cash Assistance Of Village Funds On Community Welfare In Martapura District, Banjar District, South Kalimantan - Rizky Subhan*; Junaidy Junaidy; Dewi Merdayanty (Riwayat: Educational Journal of History and Humanities, 2023)
This research was conducted with a focus on research on the effect of the effectiveness of direct village fund cash assistance on community welfare in Martapura District, Banjar Regency, South Kalimantan. With the formulation of the problem, namely how to evaluate the direct cash assistance program during the Covid 19 pandemic.The purpose of this study was to determine the effect of the effectiveness of direct village fund cash assistance on community welfare. The theory that will be used in this study uses the theory of effectiveness which consists of 8 indicators, namely timeliness, cost calculation accuracy, measurement accuracy, goal determination accuracy, choice accuracy, thinking accuracy, order accuracy and target accuracy. The method used in this research is descriptive quantitative.  The subjects of this study were recipients of direct cash assistance, which consisted of 1,787 people. Based on the Slovin formula with a confidence level of 10%, the sample consists of 96 people. Sampling using proportionate area random sampling. This study used a questionnaire, observation and documentation. In analyzing the research data using a simple linear regression hypothesis test. The results of this study show that there is an effect of the effectiveness of direct cash assistance on community welfare with a sig value of 0.000 and a magnitude of  39.6% of the variable effectiveness of direct cash assistance on community welfare.